Low molecular weight blood plasma proteome – a source of differential diagnostic biomarkers of ovarian cancer - V. Ye. Shevchenko; N. Ye. Arnotskaya; N. R. Pogosyan; O. G. Ioseliany; A. N. Gritsay (Опухоли женской репродуктивной системы, 2014)
At present, there is no screening test for the early detecting of ovarian cancer, one of the most lethal form of gynaecological malignancy in the worldwide. In this study the new methodology for the search of tumor markers of ovarian cancer, involving profiling the low-molecular blood plasma proteomes, is developed, unified and approved. The given approach included three basic components: pre-preparation of samples, matrix-assisted laser desorption / ionization time-of-flight mass spectrometry and bioinformatics software for mass spectral data processing. Opportunities and prospects of the developed approach for the detection of potential ovarian cancer markers were shown. For search of potential tumor markers, screening of 56 blood plasma samples from ovarian cancer patients and 36 benign ovarian neoplasia samples were carried out.As a result of the present research, peptides / polypeptides which can be used in future for detecting this pathology were found out.